2023
DOI: 10.5802/crphys.97
|View full text |Cite
|
Sign up to set email alerts
|

North Polar Spur/Loop I: gigantic outskirt of the Northern Fermi bubble or nearby hot gas cavity blown by supernovae?

Abstract: Radio continuum, microwave and gamma-ray images of the Milky Way reveal a conspicuous, looplike structure that fills almost half of the northern Galactic hemisphere, called Loop I. The interior of Loop I is the most conspicuous region shining in soft X-rays, whose eastern base is a remarkably bright, elongated structure seeming to emerge from the Galactic plane, dubbed the North Polar Spur (NPS). After 40 years of debates, two very different, contradictory views of Loop I/NPS are still defended: on the one han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It is worthwhile to note that the exact attribution of features in the polarized radio sky to local or global phenomena in the Galaxy is still under debate; see, e.g., Lallement (2023). Some of the loops and filaments could be caused by local supernova remnants expanding into the surrounding ambient magnetic field (Spoelstra 1973), whereas others might be related to largescale magnetized outflow from the Galactic center (Carretti et al 2013), related to the so-called "Fermi bubbles" observed in gamma rays (Ackermann et al 2014) and surrounded by "eROSITA bubbles" in X-rays (Predehl et al 2020).…”
Section: Polarized Synchrotron Emissionmentioning
confidence: 99%
“…It is worthwhile to note that the exact attribution of features in the polarized radio sky to local or global phenomena in the Galaxy is still under debate; see, e.g., Lallement (2023). Some of the loops and filaments could be caused by local supernova remnants expanding into the surrounding ambient magnetic field (Spoelstra 1973), whereas others might be related to largescale magnetized outflow from the Galactic center (Carretti et al 2013), related to the so-called "Fermi bubbles" observed in gamma rays (Ackermann et al 2014) and surrounded by "eROSITA bubbles" in X-rays (Predehl et al 2020).…”
Section: Polarized Synchrotron Emissionmentioning
confidence: 99%
“…At latitudes , this feature is approximately spatially coincident with the North Polar Spur visible in X-rays. The physical origin, or even the distance to these structures, is unknown (Lallement 2022 ) with hypotheses ranging from a local SNR (Das et al. 2020 ) to an outflow from the Galactic center (Kataoka et al.…”
Section: Observational Signaturesmentioning
confidence: 99%
“…As such, we select this sample based on LNPS's multiwavelength appearance so that we include all sight lines that may pass through the LNPS association. We chose not to include the faint southern structures that are at times associated with Loop I (Loop Is and the southern extension of Loop XII) because their connection with the northern LNPS association is not clear; it is possible that this structure is related to the southern eROSITA Bubble or separate supernovae remnants (Berkhuijsen et al 1971;Sofue & Reich 1979;Planck Collaboration et al 2016;Predehl et al 2020;Panopoulou et al 2021;Lallement 2022).…”
Section: Lnps and Northern Eb Sight Linesmentioning
confidence: 99%
“…Until recently, one strong argument against the LNPS being associated with the GC was that the LNPS had no southern Galactic counterpart. The discovery of a southern X-ray bubble (also known as the southern eB) has reignited that debate (Predehl et al 2020;Lallement 2022;Yang et al 2022).…”
Section: Introductionmentioning
confidence: 99%